2021
DOI: 10.1038/s41598-021-02154-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CT to CBCT contour mapping for radiomic feature analysis in prostate cancer

Abstract: This study provides a quantitative assessment of the accuracy of a commercially available deformable image registration (DIR) algorithm to automatically generate prostate contours and additionally investigates the robustness of radiomic features to differing contours. Twenty-eight prostate cancer patients enrolled on an institutional review board (IRB) approved protocol were selected. Planning CTs (pCTs) were deformably registered to daily cone-beam CTs (CBCTs) to generate prostate contours (auto contours). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“… 209 In particular, even for contour created by a trained radiologist, inter- and intra-observer contouring variability could significantly impact the successive radiomics extracted features, while in automatically generated contouring, despite promising results, current findings are still unripe. 210 , 211 Despite this could potentially lead to important limitations related to reproducibility, novel approaches assessing the sensitivity of RFs in relation to inter-observer variability (via the normalization and quantization of images before extraction or the use of morphological features) could limit this issue. 212 , 213 Different combination models between clinical features, imaging phenotypes, and radiomics gave better results in diagnosing PCa, but their use is still limited to clinical research.…”
Section: Discussionmentioning
confidence: 99%
“… 209 In particular, even for contour created by a trained radiologist, inter- and intra-observer contouring variability could significantly impact the successive radiomics extracted features, while in automatically generated contouring, despite promising results, current findings are still unripe. 210 , 211 Despite this could potentially lead to important limitations related to reproducibility, novel approaches assessing the sensitivity of RFs in relation to inter-observer variability (via the normalization and quantization of images before extraction or the use of morphological features) could limit this issue. 212 , 213 Different combination models between clinical features, imaging phenotypes, and radiomics gave better results in diagnosing PCa, but their use is still limited to clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…A larger patient cohort will make it difficult to replicate the results of this study due to time costs. Auto segmentation of the prostate contours through the use of artificial intelligence, deep learning, or deformable propagation could greatly reduce the time it takes run radiomics studies such as this 42 . Future work will investigate performance of automated contours in comparison to manually segmented contours for radiomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These features are described in detail in Delgadillo et al . , including the Image Biomarker Standardization Initiative (IBSI) code equivalent 31 , 42 . The full list of RFs along with their IBSI code equivalent are shown in Supplementary Table S3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If acquisition details are not perfectly matched, two different images, even of the same tissue, will yield different measurements. A number of studies have reported the impact on CT radiomics analysis caused by the variability of acquisition parameters and post-process variables [15][16][17][18] . Any algorithm or analysis based on these measurements will therefore not be reliable for use with unseen scanners.…”
Section: Introductionmentioning
confidence: 99%